Standar Operational Procedures (SOP) sebagai Kunci Pembenahan Masalah dalam Mekanisme Pelaksanaan Program Pendampingan Ekspor - Abdillah Sani (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
Many of Indonesia’s Small and Medium Enterprises (SMEs) have potential products for export. Among them, some are supplying exporters or selling products to overseas buyers who come directly to them. Not much profit they get by means of indirect exports. Therefore, since 2010 the Ministry of Trade has held an Export Assistance Program. This program applies a mixed method between activities in the classroom, mentoring in the field and consultation both directly and online. Thefacilitator or coach is Widyaiswara and practitioner, with various expertise in the field of export. This program apparently has not produced optimal results even though the curriculum has repeatedly been refined. Therefore we need a study of what the causes are. Using qualitative descriptive methods, this research traces data and documents, distributes questionnaires and conducts interviews with many parties involved. The results lead to the conclusion that the obstacles to the implementation of this program are due to the unavailability of standardized work mechanisms or Standard Operating Procedures (SOPs) that are understood together and are binding on all parties. Intensive and maximum cooperation from all stakeholders has not yet been realized and the progress of the participants’ progress to become an exporter has not been seriously worked on so that this program does not get maximum encouragement to achieve optimal results.